Examination of molecular genetic factors involved in sensitivity to breast cancer following radiation exposure - Williams, Abby J., author; Ullrich, Robert L., advisor; Bailey, Susan M., advisor (Colorado State University. Libraries, 2008)
Understanding DNA repair is not only an important aspect of cell biology, but also has important implications for the field of carcinogenesis since cancer most likely occurs from genetic damage that occurs over one's lifetime. DNA repair needs to be accurate and efficient in order for a cell to maintain genomic stability, and defects in repair systems can result in radiosensitivity. Because radiation exposure, DNA repair deficiency and telomere malfunction are associated with cancer risk, we investigated Lymphoblastoid Cell Lines (LCLs) from breast cancer patients and controls for chromosomal radiosensitivity, relative telomere length, and gene expression changes. The importance of studying peripheral blood lymphocytes from cancer patients lies in the fact that minimally invasive techniques are lacking for the detection of individuals with high risk for cancer, and that telomere length has been proposed to be useful in this regard. Identification of radiosensitivity markers would be a valuable contribution for clinicians in hopes of avoiding excessive radiation or chemotherapy treatment given to patients. Failure to adequately repair DNA damage can result in cell suicide or halting of cell cycle progression in an attempt to allow repair mechanisms to operate. If damage persists, a cell can be pushed toward transformation and the pathway of carcinogenesis. A second aspect of the current work was to study the Homologous Recombination double-strand break repair protein, Rad51D. The emerging interrelations between DNA repair and telomere maintenance also prompted us to evaluate Rad51D's role in telomere function. The final aspect of this research involved examination of how DNA repair related proteins are linked to the indirect effect of ionizing radiation exposure known as the bystander effect (BSE). We are the first to demonstrate that DNA-PKcs and ATM are required to generate, but not receive, a bystander signal. We also show that mouse embryonic fibroblasts do not generate bystander signals to neighboring cells, while their adult cell counterparts do. Taken together, this work makes important contributions to our appreciation of the many and varied roles DNA repair related proteins play in maintenance of chromosomal integrity, proper telomere function, inhibition of carcinogenesis and now, regulation of the BSE.
Keywords: breast cancer; bystander effect; DNA repair; Rad51D; radiation biology; radiation exposure; telomeres; molecular biology; cellular biology; medicine; oncology